Proceedings of the 2015 ACM on International Conference on Multimodal Interaction 2015
DOI: 10.1145/2818346.2820776
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Detection of Depression in Clinical Interviews

Abstract: Current methods for depression assessment depend almost entirely on clinical interview or selfreport ratings. Such measures lack systematic and efficient ways of incorporating behavioral observations that are strong indicators of psychological disorder. We compared a clinical interview of depression severity with automatic measurement in 48 participants undergoing treatment for depression. Interviews were obtained at 7-week intervals on up to four occasions. Following standard cut-offs, participants at each se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 24 publications
1
41
0
Order By: Relevance
“…To further assess the quality of the proposed dynamic feature sets, we compared them with the dynamic features proposed in our earlier work [41] and with alternative dynamic features that include facial movement [14], head movement [19], or prosodic features [11]. For a fair and accurate comparison between the proposed dynamic features and alternative methods, it was necessary to re-implement the alternative methods for: (1) the more challenging problem of measurement of 3-levels of depression severity (as compared to 2-classes classification), and (2) evaluating them on our clinical data.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To further assess the quality of the proposed dynamic feature sets, we compared them with the dynamic features proposed in our earlier work [41] and with alternative dynamic features that include facial movement [14], head movement [19], or prosodic features [11]. For a fair and accurate comparison between the proposed dynamic features and alternative methods, it was necessary to re-implement the alternative methods for: (1) the more challenging problem of measurement of 3-levels of depression severity (as compared to 2-classes classification), and (2) evaluating them on our clinical data.…”
Section: Resultsmentioning
confidence: 99%
“…For a fair and accurate comparison between the proposed dynamic features and alternative methods, it was necessary to re-implement the alternative methods for: (1) the more challenging problem of measurement of 3-levels of depression severity (as compared to 2-classes classification), and (2) evaluating them on our clinical data. Thus, we re-implemented previous methods as well as could be done from their description in the corresponding papers (including adapting our own work [41] to the problem of 3-levels of depression severity).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Girard and colleagues , in a longitudinal study of adult patients in treatment for depression, found that head motion velocity increased as they recovered from depression. Dibeklioglu and colleagues (Dibeklioglu et al, 2015) reported related findings for both head and face. In addition to communicating affect, head motion serves regulatory functions.…”
mentioning
confidence: 93%